On the effectiveness of macroprudential policy - Miguel Ampudia; Marco Lo Duca; Mátyás Gábor Farkas; Gabriel Pérez-Quirós; Mara Pirovano; Gerhard Rünstler; Eugen Tereanu (European Central Bank (ECB), 2021)
Since the global financial crises, many countries have implemented macroprudential policies with the aim to render the financial system more resilient to shocks and limit the procyclicality of the financial system. We present theoretical and empirical evidence on the effectiveness of macroprudential policy, on both, financial stability and economic growth focussing on capital measures and borrower-based measures.
Keywords: G21; 330; Macroprudential policy; financial stability; bank capital; borrowers